Understanding the causes and effects of defects in advanced sheet moulding compounds - Wilson, Daniel John (2024)
Discontinuous fibre reinforced composites such as Sheet Moulding Compounds (SMCs) have the potential to solve many of the problems inherent in conventional continuous fibre composites. Composed of shorter, randomly-orientated fibre tows, these materials are able to flow into complex geometries with minimal preparation and have rapid curing times. However, they come with their own disadvantages, including inferior mechanical properties and high variability. They also contain defects, defined as an imperfection in the material which results in a deviation from the design specification. The observed defects take the form of blisters and pockmarks on the part surface, and their causes and effects are currently not well understood. This research aims to investigate these defects to identify why they form and how they influence the mechanical performance of SMC parts.